THE PURPOSE OF PRESERVING LIFE AND OFFSPRING SURVIVAL, A COMPARATIVE STUDY BETWEEN ISLAMIC AND WESTERN THOUGHT - CHTAIBA, Dr. JAMAL; OUHNA, Dr. DRISS (International Journal of Multidisciplinary Research and Studies, 2022)
Preserving life and preserving the human race is one of the essential supreme goals of all religions and laws and approved - in the sentence - by all systems and laws. This research paper seeks to discuss this great purpose from two aspects; The side of nothingness and the side of existence. From the first aspect, scholars and thinkers from various walks of life endeavored to preserve human life from aggression by devastating wars and similar deadly diseases and famines. On the other hand, theorizing was done to promote the human race by providing the basic needs of human beings and saving the human race from loss and corruption.